PROSPECTS OF AN AUTOMATED COMPUTER SOFTWARE IMPLEMENTATION FOR PREDICTION OF COURSE AND TREATMENT IN PATIENTS WITH DIFFERENT FORMS OF ODONTOGENIC MAXILLARY SINUSITIS - Voloshan, O.O.; Grigorov, S.M.; Demyanyk, D.S.; Ruzin, G.P.; Lokes, K.P. (World of Medicine and Biology, 2019)
It has been suggested to implement automated computer software for predicting the course and treatment in patients with various forms of odontogenic maxillary sinusitis (OMS) into clinical practice. The results of 153 patients’ (prospective group) treatment were analyzed with the use of medical expert systems (MES), gender - age distribution, clinical - anamnestic data, type of surgery and comparative characteristics of complications with retrospective group. Reliable computer diagnoses were obtained, suggested by the MES, which coincided with the final clinical diagnoses in 97% of cases and individualized comprehensive treatment was applied to each clinical case. By means of MES, with regard to the prognosis of diagnosis and the comprehensive treatment variant, we have managed to reduce the proportion of actual complications depending on the clinical OMS form from 9, 22% (19 patients) to 2.6% (4 patients). The initial results analysis established the efficiency and prospects of using the automated “Easy-sinus 1.01” MES in the treatment of patients with various OMS forms.
Keywords: odontogenic maxillary sinusitis; medical expert systems; diagnosis and treatment; computer-based disease prediction